Communication strategies for the spring/summer 2021 collections - Chen, Luciana (2022)
The study focuses on the communication strategies of Dior, Jacquemus, Miu-Miu and Moschino for the spring/summer 2021 collections, specifically, on the audience's modes of presence in each fashion show in the pandemic. Based on audiovisuals related to the exhibitions of each brand on the virtual platform YouTube and based on discursive semiotics, it is expected that the research contribute to reflections about the body in the ways of communicating fashion.